Preparation method of electrothermal synergistic noble metal-perovskite catalyst
Through the preparation of electrothermal synergistic precious metal-perovskite catalysts, the problem of insufficient catalytic activity under low temperature conditions in traditional catalytic oxidation technology is solved, and the effect of efficiently removing VOCs at low voltage is achieved, reducing energy consumption and cost.
Patent Information
- Application Number
- CN202411843100.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional catalytic oxidation technology has low catalytic activity under low temperature conditions and high energy consumption, making it difficult to effectively remove volatile organic compounds (VOCs).
The preparation method of the electrothermal synergistic noble metal-perovskite catalyst is adopted to form a conductive noble metal-perovskite composite catalyst by recombining the noble metal with samarium-based cobalt-based or manganese-based perovskite to enhance its low-temperature oxidation activity.
Under low voltage and low power conditions, the catalyst exhibits excellent oxidation activity, effectively reducing energy consumption and cost, improving the practicality and economicality of the catalyst, and solving the problem of insufficient catalytic activity in low temperature environments.
Smart Images

Figure CN119657168A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and in particular to a method for preparing an electrothermal synergistic noble metal-perovskite catalyst. Background Art
[0002] In recent years, with the acceleration of industrialization and the improvement of urbanization, the emission of volatile organic compounds (VOCs) has increased significantly. As an important type of atmospheric pollutant, VOCs not only have adverse effects on human health, but also participate in photochemical reactions, leading to the generation of ozone and fine particulate matter, exacerbating the problem of air pollution. Therefore, the efficient removal and treatment of VOCs has become a key challenge in the field of environmental protection. The current mainstream VOCs treatment methods include adsorption, combustion, condensation and catalytic oxidation. Among them, catalytic oxidation is widely used in the treatment of VOCs due to its low energy consumption and wide range of applications. However, traditional catalytic oxidation technology relies on high temperature conditions, consumes a lot of energy and has low catalytic activity at low temperatures. Therefore, it is urgent to develop efficient and low-temperature VOCs catalytic oxidation technology.
[0003] As an emerging catalyst carrier, perovskite materials have attracted widespread attention in recent years due to their unique structure and excellent oxygen ion migration ability. The perovskite structure can accommodate a variety of different metal elements, which enables it to have good oxygen migration and oxygen storage capacity under electrically driven conditions, and is suitable for low-temperature oxidation reactions. However, perovskite materials still face problems such as insufficient low-temperature activity and poor stability in practical applications, especially when facing complex pollutants such as VOCs, and their activation ability and electrically driven migration performance need to be further improved. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings existing in the prior art, and a method for preparing an electrothermal synergistic precious metal-perovskite catalyst is proposed. The prepared catalyst not only achieves the effect of efficient removal of VOCs, but also overcomes the problem that traditional catalysts have poor catalytic activity under low temperature environment. It can show excellent oxidation activity under low voltage, greatly reduces energy consumption and cost, enhances the practicability and economy of the catalyst, and is of great significance to energy conservation and environmental protection.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing an electrothermal synergistic noble metal-perovskite catalyst comprises the following steps:
[0007] S1. directly mix a certain proportion of samarium salt, cobalt or manganese salt, citric acid and a small amount of deionized water, and stir for a period of time to form a viscous slurry to obtain a mixture;
[0008] S2, directly placing the mixture obtained in S1 in a muffle furnace for calcination, heating the temperature to a certain temperature at a certain heating rate, and maintaining the temperature for a period of time, so as to obtain a conductive cobalt-based or manganese-based perovskite;
[0009] S3. Add the cobalt-based or manganese-based perovskite obtained in S2 to the precious metal salt solution, stir for 5 to 10 minutes, then add ethanol and 30% hydrogen peroxide, continue stirring, filter, dry, and calcine to obtain a conductive precious metal-perovskite composite catalyst.
[0010] Preferably, in step S1, the samarium salt is a mixture of one or more of samarium nitrate, samarium chloride, samarium acetate and samarium sulfate.
[0011] Preferably, in step S1, the cobalt salt is a mixture of one or more of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt acetate.
[0012] Preferably, in step S1, the manganese salt is a mixture of one or more of manganese chloride, manganese nitrate, manganese sulfate and manganese acetate.
[0013] Preferably, in step S1, the molar ratio of the samarium salt, cobalt or manganese salt and citric acid is 1:1:(1-5); the content of the small amount of deionized water injected is 5%-30% of the total mass of the samarium salt, cobalt or manganese salt and citric acid; the stirring time is 10-120 min, and the stirring rate is 100-1000 r / min.
[0014] Preferably, in step S2, the calcination heating rate is 1-10°C / min; the constant temperature maintained during calcination is 700-900°C, and the maintenance time of the calcination constant temperature stage is 2-8h.
[0015] Preferably, in step S3, the noble metal salt is a mixture of one or more of nitrates and chlorides of palladium, platinum, rhodium and silver, and the amount of the noble metal salt is 0.1 wt% to 5 wt% of the perovskite.
[0016] Preferably, in step S3, the mass ratio of the perovskite to ethanol and 30% hydrogen peroxide is 1:(10-100):0.1.
[0017] Preferably, in step S3, the continuous stirring time is 10 to 120 min, and the stirring rate is 100 to 1000 r / min.
[0018] Preferably, in step S3, the drying temperature is 60-80° C., the drying time is 6-8 hours, the roasting temperature is 500-600° C., and the roasting time is 3-5 hours.
[0019] By adopting the above technical solution: precious metals and perovskites are compounded to improve the low-temperature activity of perovskite catalysts. Precious metal materials (such as platinum, palladium, etc.) have excellent catalytic activity and surface active site activation ability, which can effectively improve the activity of reaction sites on the surface of perovskites, thereby enhancing the oxygen migration rate of perovskites under electrically driven conditions. Through the composite design of precious metals and samarium cobalt-based or manganese-based perovskites, the catalyst of the present invention can achieve high-efficiency catalytic activity under low voltage and low power conditions, breaking through the technical limitations of traditional thermal catalytic processes for oxidizing VOCs at low temperatures, effectively improving the low-temperature activity and stability of perovskite materials, and providing innovative solutions for low-temperature purification of VOCs. With the further development and application promotion of this technology, it is expected that the catalyst will show broad application prospects and significant economic benefits in the environmental protection industry, especially in the field of low-temperature exhaust gas treatment.
[0020] Among them, the addition of the precious metal of the present invention can greatly reduce the activation energy of the reaction, and at the same time, under electrothermal conditions, the surface active sites activated by the precious metal promote the effective migration of lattice oxygen. Electric drive not only improves the oxygen migration ability of perovskite, but also ensures its excellent catalytic oxidation effect under low temperature conditions, so that VOCs can be oxidized and decomposed at a lower temperature. This feature enables the catalyst of the present invention to exhibit excellent oxidation activity at low voltage, greatly reducing energy consumption and cost, enhancing the practicality and economy of the catalyst, and is of great significance to energy conservation and environmental protection.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention realizes the synergistic effect between perovskite and precious metals through the electrothermal synergistic catalytic effect, which significantly improves the oxidation activity of the catalyst at low temperature.
[0023] 2. The introduction of the conductive perovskite material in the present invention improves the electrothermal coupling performance of the catalyst, thereby greatly enhancing the stability of the catalyst in industrial applications.
[0024] 3. The present invention uses the auxiliary effects of hydrogen peroxide and ethanol to evenly distribute the precious metal particles on the surface of the perovskite, thereby reducing the amount of precious metal used while achieving excellent catalytic performance and reducing the preparation cost of the catalyst.
[0025] 4. Compared with the traditional catalyst preparation method, the process steps of the present invention are simplified, which not only reduces the steps but also improves the preparation efficiency, and is convenient for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The XRD diagram of the composite catalyst electrothermal synergistic catalyst prepared in Example 1 of the present invention;
[0027] Figure 2 Performance diagram of electrothermal catalytic oxidation of ethyl acetate by catalysts prepared for all embodiments of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] (1) Mix 4.44 g of samarium nitrate, 2.91 g of cobalt nitrate and 7.68 g of citric acid, then add 1.503 g of deionized water dropwise and stir for 120 min until the mixture becomes a viscous slurry;
[0031] (2) placing the slurry in a muffle furnace, heating it to 800° C. at a heating rate of 3° C. / min, and maintaining the temperature for 5 hours to obtain a product;
[0032] (3) adding the product to 5.14 g of a 0.5 wt % palladium chloride solution, stirring for 5 min, adding 40 g of ethanol and 0.26 g of 30 wt % hydrogen peroxide, stirring at 800 r / min for 30 min, filtering, and drying at 70° C. to obtain a catalyst precursor;
[0033] (4) The obtained catalyst precursor was calcined at 500°C for 3 hours to obtain an electrothermal synergistic Pd / SmCoO3 composite catalyst.
[0034] The XRD pattern of the catalyst prepared in Example 1 is as follows: Figure 1 As shown in the figure, the characteristic diffraction peaks of Pd and SmCoO3 can be seen, indicating that the composite material was successfully prepared, and Pd exists in the form of metal Pd on the surface of SmCoO3, which is beneficial to improve the low-temperature conductivity of the catalyst. -1 , ethyl acetate concentration is 1000mg / m 3 and 5A current conditions for electrocatalytic oxidation, such as Figure 2 As shown, the ethyl acetate removal efficiency reached 90% at 110°C, while in the absence of electricity, 340°C was required to achieve 90% ethyl acetate removal efficiency, indicating that the prepared composite catalyst exhibits excellent electrothermal synergistic VOC removal activity.
[0035] Embodiment 2:
[0036] (1) 4.44 g of samarium nitrate, 2.91 g of cobalt nitrate and 3.84 g of citric acid were mixed, and then 0.74 g of deionized water was added and stirred for 100 min until a viscous slurry was obtained;
[0037] (2) placing the slurry in a muffle furnace, heating it to 850° C. at a heating rate of 5° C. / min, and maintaining the temperature for 4 hours to obtain a product;
[0038] (3) The product was mixed with 2.57 g of 1 wt% platinum nitrate, stirred for 10 min, and then 50 g of ethanol and 0.26 g of hydrogen peroxide (30 wt%) were added, stirred at 100 r / min for 10 min, filtered, and dried at 60° C. to obtain a catalyst precursor;
[0039] (4) The obtained catalyst precursor was calcined at 550°C for 3 hours to obtain an electrothermal synergistic Pt / LaCoO3 composite catalyst.
[0040] 1 g of the catalyst prepared in Example 2 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 85% at 110℃, showing excellent VOC removal activity.
[0041] Embodiment 3:
[0042] (1) Mix 4.44 g of samarium nitrate, 2.91 g of cobalt nitrate, and 5.76 g of citric acid, then add 0.13 g of deionized water and stir for 10 min until the mixture becomes a viscous slurry;
[0043] (2) placing the slurry in a muffle furnace, heating it to 700° C. at a heating rate of 2° C. / min, and maintaining the temperature for 6 hours to obtain a product;
[0044] (3) The product was mixed with 3.22 g of 0.8 wt% rhodium chloride solution, and then 0.26 g of 30 wt% hydrogen peroxide and 120 g of ethanol were added after stirring, and the mixture was stirred at 1000 r / min for 120 min. After filtering, the mixture was dried at 80° C. to obtain a catalyst precursor;
[0045] (4) The obtained catalyst precursor was calcined at 600°C for 4 hours to obtain an electrothermal synergistic Rh / LaCoO3 composite catalyst.
[0046] 1 g of the catalyst prepared in Example 3 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 88% at 110°C, showing excellent VOC removal activity.
[0047] Embodiment 4:
[0048] (1) Mix 2.22 g of samarium nitrate, 1.45 g of cobalt nitrate, and 2.88 g of citric acid, add 0.13 g of deionized water, and stir for 60 min;
[0049] (2) placing the mixture in a muffle furnace and heating it to 750° C. at a heating rate of 7° C. / min, and calcining it for 5 h to obtain a product;
[0050] (3) The product was mixed with 1.29 g of 1 wt% silver nitrate solution, and then 0.26 g of 30 wt% hydrogen peroxide and 100 g of ethanol were added after stirring, and the mixture was stirred at 500 r / min for 100 min. After filtering, the mixture was dried at 70° C. to obtain a catalyst precursor;
[0051] (4) The obtained catalyst precursor was calcined at 500°C for 5 hours to obtain an electrothermal synergistic Ag / LaCoO3 composite catalyst.
[0052] 1 g of the catalyst prepared in Example 4 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 76% at 110°C, showing excellent VOC removal activity.
[0053] Embodiment 5:
[0054] (1) 4.44 g of samarium nitrate, 2.96 g of 50 wt% manganese nitrate and 3.84 g of citric acid were mixed, and then 0.65 g of deionized water was added and stirred for 50 min until a viscous slurry was obtained;
[0055] (2) placing the slurry in a muffle furnace, heating it to 800° C. at a heating rate of 9° C. / min, and maintaining the temperature for 3 hours to obtain a product;
[0056] (3) The product was mixed with 2.53 g of 1 wt% platinum nitrate, stirred for 10 min, and then 50 g of ethanol and 0.26 g of hydrogen peroxide (30 wt%) were added, stirred at 300 r / min for 30 min, filtered, and dried at 80° C. to obtain a catalyst precursor;
[0057] (4) The obtained catalyst precursor was calcined at 600°C for 3 hours to obtain an electrothermal synergistic Pt / LaMnO3 composite catalyst.
[0058] 1 g of the catalyst prepared in Example 5 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 80% at 110°C, showing excellent VOC removal activity.
[0059] Embodiment 6:
[0060] (1) 4.44 g of samarium nitrate, 2.96 g of 50 wt% manganese nitrate and 5.76 g of citric acid were mixed, and then 0.25 g of deionized water was added and stirred for 110 min until a viscous slurry was obtained;
[0061] (2) placing the slurry in a muffle furnace, heating it to 750° C. at a heating rate of 5° C. / min, and maintaining the temperature for 2 hours to obtain a product;
[0062] (3) The product was mixed with 3.17 g of 0.8 wt% rhodium chloride solution, and then 0.26 g of 30 wt% hydrogen peroxide and 100 g of ethanol were added after stirring, and the mixture was stirred at 500 r / min for 50 min. After filtering, the mixture was dried at 70° C. to obtain a catalyst precursor;
[0063] (4) The obtained catalyst precursor was calcined at 600°C for 4 hours to obtain an electrothermal synergistic Rh / LaMnO3 composite catalyst.
[0064] 1 g of the catalyst prepared in Example 6 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 82% at 110°C, showing excellent VOC removal activity.
[0065] Embodiment 7:
[0066] (1) 2.22 g of samarium nitrate, 1.45 g of 50 wt% manganese nitrate and 2.88 g of citric acid were mixed, 0.25 g of deionized water was added, and stirred for 40 min;
[0067] (2) placing the mixture in a muffle furnace and heating it to 750° C. at a heating rate of 4° C. / min, and calcining it for 5 h to obtain a product;
[0068] (3) The product was mixed with 0.25 g of 1 wt% silver nitrate solution, and then 0.26 g of 30 wt% hydrogen peroxide and 50 g of ethanol were added after stirring, and the mixture was stirred at 600 r / min for 70 min. After filtering, the mixture was dried at 80° C. to obtain a catalyst precursor;
[0069] (4) The obtained catalyst precursor was calcined at 550°C for 5 hours to obtain an electrothermal synergistic Ag / LaMnO3 composite catalyst.
[0070] 1 g of the catalyst prepared in Example 7 was used at a reaction space velocity of 12000 mL·h-1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 70% at 110°C, showing excellent VOC removal activity.
[0071] Embodiment 8:
[0072] (1) 4.44 g of samarium nitrate, 50 wt% of manganese nitrate and 7.68 g of citric acid were mixed, and then 0.5 g of deionized water was added dropwise and stirred for 70 min until a viscous slurry was obtained;
[0073] (2) placing the slurry in a muffle furnace, heating it to 900° C. at a heating rate of 6° C. / min, and maintaining the temperature for 8 hours to obtain a product;
[0074] (3) adding the product to 5.06 g of a 0.5 wt % palladium chloride solution, stirring for 15 min, adding 50 g of ethanol and 0.26 g of a 30 wt % hydrogen peroxide solution, stirring at 600 r / min for 30 min, filtering, and drying at 60° C. to obtain a catalyst precursor;
[0075] (4) The obtained catalyst precursor was calcined at 500°C for 3 hours to obtain an electrothermal synergistic Pd / LaCoO3 composite catalyst.
[0076] 1 g of the catalyst prepared in Example 8 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current, and the ethyl acetate removal efficiency reached 75% at 110°C, showing excellent VOC removal activity.
[0077] Control Example 1: Only cobalt-based perovskite is used without introducing precious metal salt, and other preparation processes are the same as those in Example 1.
[0078] 1 g of the catalyst prepared in Example 1 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 The electrocatalytic oxidation was carried out under the conditions of 5A current. The ethyl acetate removal efficiency was only 10% at 110°C, and the removal effect was poor.
[0079] Comparative Example 2: Only manganese-based perovskite was used without introducing precious metal salt, and other preparation processes were the same as those in Example 1.
[0080] 1 g of the catalyst prepared in Example 2 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3The electrocatalytic oxidation was carried out under the conditions of 5A current. The ethyl acetate removal efficiency was only 8% at 110°C, and the removal effect was poor.
[0081] Comparative Example 3:
[0082] (1) Add 2.46 g of aluminum oxide carrier to 4.92 g of 0.5 wt% palladium chloride solution, stir for 5 min, then add 40 g of ethanol and 0.26 g of 30 wt% hydrogen peroxide, continue stirring at 800 r / min for 30 min, filter, and dry at 70°C;
[0083] (2) The obtained catalyst was calcined at 500°C for 3 hours to obtain an electrothermal synergistic Pd / LaCoO3 composite catalyst.
[0084] 1 g of the catalyst prepared in Example 3 was used at a reaction space velocity of 12000 mL·h -1 , ethyl acetate concentration is 1000mg / m 3 Under these conditions, there is no electrocatalytic effect.
[0085] The test results of the above embodiments and control examples are shown in Table 1 below:
[0086] Table 1 Test results of various embodiments and control examples
[0087]
[0088] In summary, the catalyst prepared by the present invention not only achieves the effect of efficient removal of VOCs, but also overcomes the problem of poor catalytic activity of traditional catalysts under low temperature environment. It can show excellent oxidation activity under low voltage, greatly reduces energy consumption and cost, enhances the practicability and economy of the catalyst, and is of great significance to energy conservation and environmental protection.
[0089] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an electrothermal synergistic noble metal-perovskite catalyst, characterized in that: The steps include: S1. directly mix a certain proportion of samarium salt, cobalt or manganese salt, citric acid and a small amount of deionized water, and stir for a period of time to form a viscous slurry to obtain a mixture; S2, directly placing the mixture obtained in S1 in a muffle furnace for calcination, heating the temperature to a certain temperature at a certain heating rate, and maintaining the temperature for a period of time, so as to obtain a conductive cobalt-based or manganese-based perovskite; S3. Add the cobalt-based or manganese-based perovskite obtained in S2 to the precious metal salt solution, stir for 5 to 10 minutes, then add ethanol and 30% hydrogen peroxide, continue stirring, filter, dry, and calcine to obtain a conductive precious metal-perovskite composite catalyst.
2. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S1, the samarium salt is a mixture of one or more of samarium nitrate, samarium chloride, samarium acetate and samarium sulfate.
3. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S1, the cobalt salt is a mixture of one or more of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt acetate.
4. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S1, the manganese salt is a mixture of one or more of manganese chloride, manganese nitrate, manganese sulfate and manganese acetate.
5. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S1, the molar ratio of the samarium salt, cobalt or manganese salt and citric acid is 1:1:(1-5); the content of the injected small amount of deionized water is 5%-30% of the total mass of the samarium salt, cobalt or manganese salt and citric acid; the stirring time is 10-120 min, and the stirring rate is 100-1000 r / min.
6. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S2, the calcination heating rate is 1-10°C / min; the constant temperature maintained during the calcination is 700-900°C, and the maintenance time of the calcination constant temperature stage is 2-8h.
7. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S3, the noble metal salt is a mixture of one or more of palladium, platinum, rhodium, and silver nitrates and chlorides, and the amount of the noble metal salt is 0.1 wt% to 5 wt% of the perovskite.
8. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S3, the mass ratio of the perovskite to ethanol and 30% hydrogen peroxide is 1:(10-100):0.
1.
9. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S3, the continuous stirring time is 10 to 120 minutes, and the stirring rate is 100 to 1000 r / min.
10. The method for preparing an electrothermal synergistic noble metal-perovskite catalyst according to claim 1, characterized in that: In step S3, the drying temperature is 60-80°C, the drying time is 6-8h, the roasting temperature is 500-600°C, and the roasting time is 3-5h.